2015
DOI: 10.13080/z-a.2015.102.048
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fertilizer and N application rate on nitrogen and potassium leaching in cut grassland

Abstract: Although fertilization has a positive effect on agricultural productivity, its negative side effect can be the leaching of plant nutrients. Our objectives were to study the impact of fertilizer type and nitrogen application rate on the nitrogen and potassium leaching from grassland during and after the vegetative period. Within three years (2008-2011) mini-lysimeters experiment was conducted on grassland swards receiving mineral NPK, mineral PK, cattle slurry and sewage sludge based on nitrogen rate 0, 60, 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Source: own study. of 3-26.3 kg N•ha -1 was observed in the growing season and 2.8-1.8 N•ha -1 in non-growing season (Tampere et al, 2015); in both these periods, the leaching of nitrates was affected by the type of fertilisers used; -experimental work carried out using suction cups to determine nitrates in soil solution showed that from 17 to 60 kg NO 3 -N•ha -1 can leach from the pasture soil in a year depending on the age of the sward (at constant sward composition and nitrogen fertilisation of 300 kg N•ha -1 ) (Eriksen and Vinther, 2002); -based on the results of another experiment, in which the method of ceramic cups was used, it was determined that the losses of nitrates from soils of permanent grasslands used for mowing amount to only 2.1 ±0.3 kg•kg NO 3 -N•ha -1 (Smit et al, 2021); -in studies, carried out using continuous (flow proportional) soil leachate sampling, annual NO 3 -N leaching rates from pasture soil were 3.7-14.6 kg NO 3 -N•ha -1 when the soil was not fertilised with nitrogen, and 6.2-22.0 and 4.3-37.6 when different types of nitrogen fertiliser, namely urea and ammonium nitrate, were applied to it at the same rates (200 kg N•ha -1 ) (Eckard et al, 2004).…”
Section: Resultsmentioning
confidence: 87%
“…Source: own study. of 3-26.3 kg N•ha -1 was observed in the growing season and 2.8-1.8 N•ha -1 in non-growing season (Tampere et al, 2015); in both these periods, the leaching of nitrates was affected by the type of fertilisers used; -experimental work carried out using suction cups to determine nitrates in soil solution showed that from 17 to 60 kg NO 3 -N•ha -1 can leach from the pasture soil in a year depending on the age of the sward (at constant sward composition and nitrogen fertilisation of 300 kg N•ha -1 ) (Eriksen and Vinther, 2002); -based on the results of another experiment, in which the method of ceramic cups was used, it was determined that the losses of nitrates from soils of permanent grasslands used for mowing amount to only 2.1 ±0.3 kg•kg NO 3 -N•ha -1 (Smit et al, 2021); -in studies, carried out using continuous (flow proportional) soil leachate sampling, annual NO 3 -N leaching rates from pasture soil were 3.7-14.6 kg NO 3 -N•ha -1 when the soil was not fertilised with nitrogen, and 6.2-22.0 and 4.3-37.6 when different types of nitrogen fertiliser, namely urea and ammonium nitrate, were applied to it at the same rates (200 kg N•ha -1 ) (Eckard et al, 2004).…”
Section: Resultsmentioning
confidence: 87%
“…Although soil depth in the study catchment area is largely >2 m, most nutrient cycling takes place in the biologically most active top 10 cm of the soil, especially in grass swards and forages (Griffin et al 2002, Tampere et al 2015 which were dominant in the study area.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of herbs can be reduced by more than a third within two years. While P and K mainly influence the proportion of herbs, legumes are more affected by applied N. Tampere et al [97] found that high application rates above 120 kg N ha −1 led to the disappearance of white clover. These high N application rates compensated for this loss through higher grass yield but had no significant effect on total yield.…”
Section: Plant Composition and Diversitymentioning
confidence: 99%
“…The different types of organic fertilizers had only a small effect on K leaching. According to studies by Kayser and Isselstein [91] and Tampere et al [97], the application of cattle slurry alone increased K leaching losses from grassland over the years. The type of application and application during or after the growing season had no effect on K leaching.…”
Section: Potassium (K)mentioning
confidence: 99%
See 1 more Smart Citation